Students' attitude towards mathematics at the University of Évora, Portugal - Bayudan, Kenny Juntilla (2014)
Este estudo é uma tentativa de determinar a atitude dos estudantes de primeiro ano, que tiveram como objecto de estudo a matemática no primeiro semestre no ano académico de 13/14 na universidade de Évora, Portugal. Um questionário foi feito, passou por verificações de fiabilidade e validade, e serviu para reunir dados sobre a atitude dos estudantes em relação a matemática tais como a motivação, interesses, compreensão e níveis de ansiedade. Os resultados desta pesquisa mostraram que os alunos de primeiro ano normalmente têm uma atitude positiva em relação à matemática antes de entrarem na universidade. Existe uma forte correlação ente a atitude, motivação e interesse, perceção da competência e nível de ansiedade. Esta avaliação é importante para a universidade e para o seu corpo administrativo pois levanta preocupações sobre o fator aprendizagem. Também ajuda a entender a predisposição dos estudantes para a matemática e ajuda a criar hipóteses de intervenção para ajudar aqueles que tem uma atitude mais negativa em relação ao objecto de estudo; ### Abstract: Students’ Attitude towards Mathematics at the University of Évora, Portugal This study is an attempt to determine the attitude of freshmen students who were taking a math subject in the fall semester of the academic year 2013- 2014 at the University of Évora, Portugal. A questionnaire was developed, which underwent validity and reliability analyses, and used to gather data about students’ attitude towards math and their motivation, interest, perceived competence, and anxiety levels. The results of this research show that freshmen students generally have positive attitude towards mathematics prior to commencing university formation. There is a strong positive correlation between attitude and the motivation and interest, perceived competence and anxiety dimensions. This assessment is important to the university faculty and administration as it raises concern on the affective aspect of learning. It also helps them to understand the disposition of their students in math and create possible means of intervention to help those with a negative attitude towards the subject.